The Pattern of Joints Involvement in Patients with Rheumatoid Arthritis in Rheumatology Clinic Dr. Hasan Sadikin General Hospital Bandung - Pratama, Muhammad Kevin; Atik, Nur; Hamijoyo, Laniyati (Indonesian Rheumatology Association, 2017)
Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease with primary manifestation in the joints. Early management of RA will prevent further joint damage. The joint damages, result of uncontrolled disease activity, will decrease patientâs quality of life.RA should be diagnosed earlier and followed by early treatment initiation, in order to prevent further damages. This study aimed to determine the pattern of joint involvement in RA in order to made earlier diagnosis and treatment initiation.Method: This research was conducted using descriptive study design. Data were obtained using interview of RA patients who coming to Rheumatology Clinic of Dr. Hasan Sadikin General Hospital from August 2016 to October 2016. Collected data included number of joints involvement, duration of therapy, and duration of illness after diagnosed according to the criteria of ACR / EULAR 2010.Result: Ninety-seven RA patients were involved in this study. Subjects were dominantly women (87%), the highest age group was 45-49 years old (17.53%), duration of the disease <5 years (90.72%), and duration of therapy > 3 months (86%). Joint that frequently involved at the time when the diagnosis made was first proximal interphalangeal (49.50%), overall findings during the course of RA was the wrist joint (90.72%).There were different tendency of joint involvement between the gender, knee joints occured in 53,84% male subjects, while PIP joints were accounted for 52,38% infemale subjects.Conclusion: The first PIP was the most common joint involved in RA patients when the diagnosis made. The wrist joint involvement was dominantly found in overall course of RA. Knee joint involvement was majorly found in male RA patients, whereas female RA patients would suffer mostly from PIP joint involvement.Keywords: involvement pattern, joints, rheumatoid arthritis